Exploring Key Determinants of Indonesia Bank Profitability: An In-Depth Analysis - Rahayu, Sovi Ismawati; Choirunnisa, Choirunnisa (SAN Scientific, 2025)
This study aims to examine the effect of Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), Operating Costs, Operating Income (BOPO), and Financing to Deposit Ratio (FDR) on bank profitability, measured by Return on Assets (ROA). The research originates from the need to evaluate financial performance indicators that influence profitability, especially in state-owned commercial banks listed on the Indonesia Stock Exchange (IDX). These banks play a pivotal role in Indonesia's financial system, making them critical subjects for analysis. The study uses secondary data sourced from the IDX for the 2018–2020 period and applies purposive sampling to select 7 banks, resulting in 21 data samples. Data analysis involves both partial and simultaneous hypothesis testing. The findings indicate that NPF, BOPO, and FDR have a significant effect on profitability, while CAR does not. Simultaneously, all variables significantly influence ROA. Managerial implications highlight the importance of focusing on operational efficiency, managing asset quality, and optimizing credit distribution to enhance profitability. Understanding these financial ratios enables bank managers to formulate more targeted and effective strategies to improve performance and sustain long-term financial health